Experimental investigation into the structural behaviour of ultra-high performance fibre-reinforced concrete box-celled composite panels - S. Mahdi; A.H. Sheikh; M.S.Mohamed Ali; M. Elchalakani (Composites Part C: Open Access, 2022)
The present study investigates and advances on existing research on the structural performance of box-celled composite structures for its use as a wind-resistant roof system. The box-celled panel system is produced by casting ultra-high performance fibre-reinforced concrete (UHPFRC) into galvanised steel roofing profiled sheets with anchor screws and expanded polystyrene foam (EPS) placed in-situ to produce a light-weight system. Three reinforcement-based variations of the design are investigated and two panels for each variation are cast to produce six specimens. The structural responses of the variations as one-way panels under three-point flexure are experimentally studied for both positive and negative bending moment capacities. Test specimens showed flexural failure with significantly ductility and post-failure load capacity, and anchor screws preventing full delamination of steel profile and shear failure. Analysis based on the test results confirmed that the proposed system is compliant to various design standards based on upper limits for combined loading actions, and permissible deflections, highlighting its optimal performance.